The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/aah.10138
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus dysgalactiae: A Pathogen of Feral Populations of Silver Carp from a Fish Kill Event

Abstract: In August 2018, a series of large fish kills involving only Silver Carp Hypophthalmichthys molitrix occurred on the Mississippi River in northern Louisiana. Clinical signs observed in moribund animals included erratic swimming behavior, such as spiraling and spinning at the surface. A moribund specimen was captured by dip net near the surface at Lake Providence Landing in East Carroll Parish, northern Louisiana, and was submitted for analysis. An aseptic necropsy was performed, and diagnostic procedures, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…equisimilis isolated from animals. The MLSA also supports the existence of fish-specific clades within the subspecies (Porcellato et al 2021;Hawke et al 2021). Further investigation, including incorporation of additional isolates into MLSA and virulence testing, complemented with whole genome phylogenetic analysis will better define these genetic groups and their importance in fish disease.…”
Section: Multilocus Sequence Analysismentioning
confidence: 65%
See 3 more Smart Citations
“…equisimilis isolated from animals. The MLSA also supports the existence of fish-specific clades within the subspecies (Porcellato et al 2021;Hawke et al 2021). Further investigation, including incorporation of additional isolates into MLSA and virulence testing, complemented with whole genome phylogenetic analysis will better define these genetic groups and their importance in fish disease.…”
Section: Multilocus Sequence Analysismentioning
confidence: 65%
“…Each housekeeping gene fragment was aligned by MUSCLE with default settings in Geneious Prime 2022.0.2 to corresponding sequences from the fish-associated S. dysgalactiae strain STC3 (Heckman et al 2020; accession numbers MN955921.1, MN955970.1, MN956019.1, MN956068.1, MN956117.1, MN956166.1, MN956215.1, MN956264.1, and MN956313.1) and trimmed to the shared sequence length. A representative trimmed sequence of each housekeeping gene was used in BLAST searches of a localised database populated by the 44 S. dysgalactiae reference strains used previously for S. dysgalactiae MLSA by Hawke et al (2021). The silver carp (Hypophthalmichthys molitrix) strain LADL18-050A was also included in analysis (Hawke et al 2021).…”
Section: Multilocus Sequence Typing Of S Dysgalactiaementioning
confidence: 99%
See 2 more Smart Citations
“…The subspecies SDSD has been considered strictly an animal pathogen, and it is commonly associated with bovine mastitis ( Rato et al, 2013 ) and infectious arthritis in sheep ( Smistad et al, 2021 ) and septicemia in vampire bats ( Mioni et al, 2018 ). SDSD has been considered an important pathogen in aquaculture systems worldwide ( Maekawa et al, 2020 ; Hawke et al, 2021 ). Phylogenetic studies based on the sodA gene revealed that isolates from human blood cultures are closely related to SDSD from the fish host, suggesting that SDSD represents an important potential causative agent of zoonoses ( Koh et al, 2009 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%